Economics of tractor ownership under rainfed agriculture with applications in Ghana - Houssou, Nazaire; Diao, Xinshen; Kolavalli, Shashidhara (International Food Policy Research Institute, 2014)
This paper assesses whether tractor investment is a rational and profitable decision for farmers using firm investment theory and tractor owner survey data collected in 2013. Under erratic rainfalls, timeliness of farming operations is critical for farmers. Based on the hypothesis that owning a tractor and hiring tractor services are not necessarily perfect substitutes for farmers with relatively large farm sizes, this paper assesses whether mechanization services can be profitable for the private sector in Ghana. It particularly addresses whether farmer-to-farmer service provision is a viable alternative to current programs, which should be promoted by policymakers for scaling up agricultural mechanization in the country.